Biogenesis of Iron–Sulfur Clusters and Their Role in DNA Metabolism - Shi, Ruifeng; Hou, Wenya; Wang, Zhao-Qi; Xu, Xingzhi (Frontiers in Cell and Developmental Biology, 2021)
Iron–sulfur (Fe/S) clusters (ISCs) are versatile protein cofactors that require many components for their synthesis, transfer, and insertion into target proteins. Mitochondrial ISC assembly is the foundation of all cellular ISCs. The maturation of cytosolic and nuclear Fe/S proteins is accomplished by cooperation between the mitochondrial ISC and the cytosolic Fe/S protein assembly (CIA) systems. ISCs are needed for diverse cellular functions, including nitrogen fixation, oxidative phosphorylation, ribosome assembly, and mitochondrial respiratory pathways. Recent research advances have confirmed the presence of different ISCs in enzymes that are involved in nucleic acid metabolism, including helicases, nucleases, primases, DNA polymerases, and glycosylases. Here we outline the synthesis of mitochondrial, cytosolic and nuclear ISCs and highlight their functions in DNA metabolism.